PP.32.21: CLINICAL USE OF MAGNETIC RESONANCE IMAGING IN EVALUATING OF BRAIN AND PITUITARY IN INDIVIDUALS WITH ARTERIAL HYPERTENSION PRACTICING ACTIVE PHYSICAL CULTURE AND SPORTS. (June 2015) - Belichenko, O.; Smolensky, A.; Vorontsov, V.; Averkieva, E.; Vladimirova, V.; Tarasov, A.; Mikhailova, A.; Babaeva, A.
Abstract : Objective: To study MRI diagnostic possibilities in evaluating of brain and pituitary in individuals with hypertension practicing active physical culture and sports. Design and method: MRI was performed in 43 males and 27 females. First group included 44 individuals practicing active physical culture and sports (19 – 35 years old); second group included 26 healthy volunteers (18–30 years old). Persons in both groups had normal parameters of blood examination, blood pressure, electrocardiogram, but after exercise stress demonstrated transitory arterial hypertension (AH) 155–170/95–105. Standard MRI included flair-, T1-, T2-weighted images, and MRI with contrast enhancement. Results: We found that brain changes are more often in 1st than in 2nd group. Mild hydrocephaly (widening of subarachnoid spaces and ventricles) was found in 15 persons in 1st group (34%), and in 5 persons in 2nd group (19%). Arachnoid cysts were found in 8 persons (18%) in 1st group and in 1 person in 2nd group (4%). In 4 persons in 1st group we found signs of old hematomas (9%). In 3 persons of 1st group solitary cysts sized 6–12 mm of white matter were found (7%). In 1st group pituitary microadenomas were found in 2 women, diffuse pituitary hyperplasia - in 8 women, empty sella – in 4 women and 1 man. In 2nd group pituitary microadenomas were found in 1 women, diffuse pituitary hyperplasia - in 4 women, empty sella – in 1 women. Thus, we found pituitary changes: in 1st group - 34%, in 2nd group – 23%. In clinical status 32 persons of the 1st group marked headache during physical exercises. Some women with pituitary changes had increased prolactin level and menstrual disturbances. All these patients received appropriate treatment and dynamic examination. Conclusions: MRI is effective method of evaluation of brain and pituitary in individuals practicing active physical culture and sports, to find clinically silent changes. These data are important in finding clinically silent changes, planning training regimen and prophylactic measures application.